Shrinking cities in Australia, Japan, Europe and the USA: From a global process to local policy responses - Martinez-Fernandez, Cristina; Weyman, Tamara; Fol, Sylvie; Audirac, Ivonne; Cunningham-Sabot, Emmanuèle; Wiechmann, Thorsten; Yahagi, Hiroshi (Progress in planning, 2016)
•“Urban decline” and “shrinking cities” are interrelated but different phenomena. The first, imbued in Fordist or modernist urban development and planning thought, is a localised and episodic problem assumed soluble through rational planning. The second, resulting from the great post-Fordist transformation is global and a glocal planning challenge in the context of 21st century capitalism.•Shrinking cities is a global phenomenon but anchored at the national and local levels in its particular manifestations. Policy responses vary by each country's welfarist history and by the global forces (tertiarisation, suburbanisation, deindustrialisation, ageing, international migration) behind shrinkage.•Shrinking cities require measures tailored to a comprehensive territorial strategic approach employing a multitude of efforts, such as greening, revitalisation, economic development, and social inclusion.•Policy development for shrinking cities requires a coordinated approach at the local, regional, national and supra-national level, under a governance system that encourages inclusive and sustainable growth.•Employment, one of the most critical areas for shrinking cities, could benefit from regional employment pacts based on new governance models whereby stakeholders cooperate as equal partners and foster local empowerment. Shrinking cities can be considered as one of the most critical challenges of contemporary urban societies. Recently, this phenomenon has been the subject of growing interest both in terms of research and from an urban policy point of view. In this paper we argue that urban shrinkage and policy responses depend on the combination of global processes and local configurations. Based on a study of shrinking cities in Australia, Japan, Germany, the UK, France and the USA, this paper first aims to explore the global process of urban shrinkage in different contexts. While the phenomenon is global it is anchored at the local level and subject to particular manifestations. After analyzing the general trends of urban shrinkage in the six countries considered, the second aim of this paper is to study the way in which policies implemented in shrinking cities differ in the various national contexts. This symposium argues that policy responses need to consider both the global forces behind shrinkage and the local context where particular characteristics are found. There are however three common areas where local actors in shrinking cities tend to focus their strategies and programs: community resilience; urban regeneration strategies; and tackling the social effects of urban shrinkage.